2017
DOI: 10.1186/s13049-017-0417-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia induced alteration of repolarization - impact on acute and long-term outcome: a prospective cohort study

Abstract: BackgroundThe effects of target temperature management (TTM) on the heart aren’t thoroughly studied yet. Several studies showed the prolongation of various ECG parameters including Tpeak-Tend-time under TTM. Our study’s goal is to evaluate the acute and long-term outcome of these prolongations.MethodsIn this study we included patients with successful resuscitation after cardiac arrest who were admitted to the Charité Virchow Klinikum Berlin or the Heart and Vascular Centre of the Ruhr University Bochum between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Gachoka et al 15 reported none of 55 patients undergoing targeted temperature management developed Torsades de pointes or ventricular tachycardia. Ulmenstein et al 8 reported 13.7% of 95 patients had ventricular tachycardia and ventricular fibrillation, and Rosol et al, 9 the largest study to date, reported 11.3% of 193 patients developed ventricular tachycardia, ventricular fibrillation, or Torsades de pointes. Both latter studies showed no statistical difference in QT or QTc interval between those with and without ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gachoka et al 15 reported none of 55 patients undergoing targeted temperature management developed Torsades de pointes or ventricular tachycardia. Ulmenstein et al 8 reported 13.7% of 95 patients had ventricular tachycardia and ventricular fibrillation, and Rosol et al, 9 the largest study to date, reported 11.3% of 193 patients developed ventricular tachycardia, ventricular fibrillation, or Torsades de pointes. Both latter studies showed no statistical difference in QT or QTc interval between those with and without ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the QRS interval is noted to significantly decrease from hypothermia to after cessation of treatment. However, it is not noted to be associated with arrhythmias and likely to be a benign finding 8,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTc prolongation is common during therapeutic hypothermia, which is conducted for neuroprotection after ventricular fibrillation and ventricular tachycardia cardiac arrests. Hypothermia affects the cardiac cell membrane via electrolyte disturbances in potassium, magnesium, calcium, and sodium, which in turn cause prolongation of ventricular repolarization and the possibility of ventricular arrhythmias [ 1 , 3 ]. The physiologic effects of TTM along with the use of class III antiarrhythmic drugs (i.e., amiodarone) for ventricular tachycardia/ventricular fibrillation cardiac arrests can lead to QTc prolongation, which can in turn potentiate fibrillation and malignant arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have neuroprotective effects through reduced brain metabolism, decreased neural apoptosis, decreased production of free radicals, and overall decreased inflammation. However, it also has several adverse cardiovascular effects due to its impact on electrolytes and the stability of the cardiac membrane, potentially leading to QTc prolongation and possible arrhythmias [ 1 3 ]. QTc prolongation is a known finding during hypothermia, and it is negatively correlated with temperature (i.e., lower temperatures are associated with prolonged QTc) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%